Pittosporum Undulatum and Hedychium Gardnerianum: nutritive value and secondary metabolites on cattle reproductive performances - Nunes, Hélder Patrício Barcelos (2014)
Hedychium gardnerianum (HG) and Pittospporum undulatum (PU) are invasive plants all over the world, being in the Azores supplied to cattle on periods of shortage food. As these plants produce secondary metabolites, including a diverse range of phytochemicals compounds, the aim of the presente study is to identify how these metabolites can be related to animal’s reproductive performances. For such purpose, plants were harvested on winter, compounds extracted by method of decoction and analysed by combination of liquid chromatography and mass spectrometry as well as highperformance liquid chromatography. For nutritive evaluations, Van Soest and Weende methodologies were used. In HG quercetin-3, 4'-di-O-betaglucopyranoside, myricetin rhamnoside, quercetin rhamnoside, and gibberellin A1 and A8 were identified, while for PU were found cafeic acid derivatives, including dicaffeoylquinic acid and caffeoylquinic acid. In nutritional terms, these plants can be considered as poor, presenting percentages of dry matter (DM%) of 16.34% and 40.39%, respectively for HG and PU. Values for ash 10.4%, crude protein (CP) 7.75%, neutral detergent fiber (NDF) 64.5, acid detergent fiber (ADF) 34.69%, acid detergent lignin (ADL) 3.47% and ether extract (EE) 2.03% were found for HG. For PU values were ash 6.64%, CP 6.11%, NDF 43.84%, acid ADF 35.57%, ADL 3.56% and EE 2.71%. This study clearly indicated that, besides their low nutritive values, these plants can be used to feed ruminants, especially when pasture lacks. Nevertheless, as some compounds, namely the caffeoylquinic and dicaffeoylquinic acids, are known to be associated to physiological reproductive mechanisms, one could speculate that these compounds can be directly or indirectly associated to reproductive performances in bovine fed with these plants.